Can a short intervention focused on gravitational waves and quantum physics improve students' understanding and attitude? - Choudhary, R.; Foppoli, A.; Kaur, T.; Blair, D.; Zadnik, Marjan; Meagher, R. (Institute of Physics Publishing, 2018)
The decline in students' interest in science and technology is a major concern in the western world. One approach to reversing this decline is to introduce modern physics concepts much earlier in the school curriculum. We have used the context of the recent discoveries of gravitational waves to test the benefits of one-day interventions, in which students are introduced to the ongoing nature of scientific discovery, as well as the fundamental concepts of quantum physics and gravitation, which underpin these discoveries. Our innovative approach combines role-playing, model demonstrations, single photon interference and gravitational wave detection, plus simple experiments designed to emphasize the quantum interpretation of interference. We compare understanding and attitudes through pre and post testing on four age groups (school years 7, 8, 9 and 10), and compare results with those of longer interventions with Year 9. Results indicate that neither prior knowledge nor age are significant factors in student understanding of the core concepts of Einsteinian physics. However we find that the short interventions are insufficient to enable students to comprehend more derived concepts.